The impact of molecular profile on the lymphatic spread pattern in stage III colon cancer - Song, Jihyung (Cancer Sci, 2021)
The anatomical spread of lymph node (LN) metastasis is of practical importance in the surgical management of colon cancer (CC). We examined the effect of KRAS, BRAF, and microsatellite instability (MSI) on LN count and anatomical spread pattern in stage III CC. We determined KRAS, BRAF, and MSI status from stage III CC patients. Biomarker status was correlated with LN count and anatomical spread pattern, which was classified as sequential or skipped. Relapse‐free survival (RFS) was estimated using Kaplan‐Meier method, and correlations were assessed using log‐rank and Cox regression analyses. We analyzed 369 stage III CC patients. The proportion of KRAS mutant (mt), BRAF mt, and MSI‐high (H) were 44.2% (163/344), 6.8% (25/344), and 6.8% (25/344), respectively. The mean number of metastatic LN was higher in microsatellite‐stable (MSS) compared with MSI patients (3.5 vs. 2.7, P = .0406), although no differences were observed in accordance with KRAS or BRAF status. Interestingly, patients with BRAF mt and MSI‐H were less likely to harbor skipped metastatic LN (9.3% vs 20% and 4% vs 10.5% compared with BRAF wild‐type (wt) and MSS, respectively), but KRAS status did not predict anatomical spread pattern. Patients with KRAS wt and MSI‐H showed superior RFS compared with KRAS mt and MSS patients, respectively, whereas BRAF status did not affect RFS. Differences exist in the anatomical pattern of invaded LN in accordance with the molecular status of stage III CC. Patients with MSI‐H CC have less invaded and skipped LN, suggesting that a tailored surgical approach is possible.